2021
DOI: 10.1002/jbm.a.37337
|View full text |Cite
|
Sign up to set email alerts
|

Rat peri‐implant soft tissue specifically expressedCXCL2on titanium implant during wound healing

Abstract: Many of genes specifically expressed in peri-implant soft tissue (PIST) selected by microarray analysis are involved in the inflammatory response. This study investigated the gene expression and localization of PIST-specific inflammatory markers in PIST during wound healing. Pure titanium implants were implanted into the rat upper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, the cytokine levels of VEGF, PDGF-AA/BB, FGF-2, G-CSF, and GM-CSF in peri-implantitis sites were significantly higher than those in healthy implant sites. VEGF has the function of increasing angiogenesis and vascular permeability [ 35 ]. A histological study showed that VEGF was highly expressed in peri-implantitis soft tissue, and it was also positively correlated with peri-implant pocket depth [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cytokine levels of VEGF, PDGF-AA/BB, FGF-2, G-CSF, and GM-CSF in peri-implantitis sites were significantly higher than those in healthy implant sites. VEGF has the function of increasing angiogenesis and vascular permeability [ 35 ]. A histological study showed that VEGF was highly expressed in peri-implantitis soft tissue, and it was also positively correlated with peri-implant pocket depth [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections of gingival tissues including epithelium, lamina propria, and muscle layer that were present on the wire were cut and subjected to hematoxylin and eosin or enzymatic immunohistochemical staining as described previously 18) . The sections were first incubated with monoclonal antibodies (mAbs) against Ly6G (EPR22909-135; Abcam, Cambridge, UK), CD3 (SP7; Abcam), CCL5 (BS-1324R; Bioss, Boston, MA, USA), or control rabbit IgG (EPR25A; Abcam) and subsequently with biotinylated anti-rabbit IgG (Vector Laboratories, Burlingame, CA, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%